2020
DOI: 10.1039/c9cp06161d
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the hydration structure of sodium and potassium ions: taking additional steps on Jacob's Ladder

Abstract: The ability to reproduce the experimental structure of water around the sodium and potassium ions is a key test of the quality of interaction potentials due to the central importance of these ions in a wide range of important phenomena.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 73 publications
4
87
0
Order By: Relevance
“…The use of 23 Na NMR relaxation and diffusion as probes of solution viscosity and confinement level in biomolecular samples benefits from the advantageous properties of 23 Na nuclei, for example their relatively large gyromagnetic ratio and their 100% natural abundance, increasing the sensitivity of NMR experiments 16,30 . Besides, the high degree of symmetry of the sodium ion and its hydration layer dramatically reduces the EFG tensor at the site of 23 Na nuclei and the consequent reduction in the quadrupolar relaxation rate of 23 Na further improves the sensitivity and resolution of 23 Na NMR spectra 17,31 . Our data revealed that the 23 Na NMR relaxation of sodium ions has the further advantage of being more sensitive to subtle changes in the viscosity when compared with 17 O NMR relaxation of water molecules (Figure 2c).…”
Section: Discussionmentioning
confidence: 76%
“…The use of 23 Na NMR relaxation and diffusion as probes of solution viscosity and confinement level in biomolecular samples benefits from the advantageous properties of 23 Na nuclei, for example their relatively large gyromagnetic ratio and their 100% natural abundance, increasing the sensitivity of NMR experiments 16,30 . Besides, the high degree of symmetry of the sodium ion and its hydration layer dramatically reduces the EFG tensor at the site of 23 Na nuclei and the consequent reduction in the quadrupolar relaxation rate of 23 Na further improves the sensitivity and resolution of 23 Na NMR spectra 17,31 . Our data revealed that the 23 Na NMR relaxation of sodium ions has the further advantage of being more sensitive to subtle changes in the viscosity when compared with 17 O NMR relaxation of water molecules (Figure 2c).…”
Section: Discussionmentioning
confidence: 76%
“…For example, our results for Na + and K + are in good agreement with recent AIMD simulations conducted with the strongly constrained and appropriately normed (SCAN) meta-GGA functional for complex condensed phase systems. 19 A comparison of the ion-water RDFs obtained from AIMD (PBE-D3) and classical MD (Madrid-2019) are also reported in Fig. S1 of ESI.…”
Section: Solvation Structurementioning
confidence: 99%
“…13,14 An important contribution to this field was the development of ab initio MD (AIMD), where forces are derived from the electronic structure, 15,16 usually in the framework of density functional theory (DFT), 17 which provides the capability of studying non-additivity effects in the dynamics of ions solvation shells. AIMD simulations, using the Car-Parrinello and Born-Oppenheimer schemes, of cations [18][19][20][21][22][23] and anions, 24,25 have been mostly conducted on an isolated ion in pure liquid water, with no counterions in solution. Electrolyte solutions, on the other hand, have been subject to only a few AIMD studies, including the characterization of the dissociation of the NaCl in water, 26 the cooperative ionic effects are of the Na + and Cl À on the hydrogen bonding network, 27 and the influence of a static electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…These can be attributed to the fact that it is know that uncorrected revPBE-D3 is too repulsive on the first hydration shell around the sodium cation. 23,24 This results in the water molecules residing further away from the sodium. This explains why the peaks in the NaOH PMF are shifted by a similar amount and why too much contact pair formation is observed relative to the NN-MD calculation.…”
Section: Resultsmentioning
confidence: 99%